2020
DOI: 10.1186/s12917-020-02294-7
|View full text |Cite
|
Sign up to set email alerts
|

Field trial to evaluate the effect of an intranasal respiratory vaccine protocol on bovine respiratory disease incidence and growth in a commercial calf rearing unit

Abstract: Background: Bovine respiratory disease (BRD) continues to be great challenge in calf rearing units. The urgent need to decrease the use of antibiotics and increase animal welfare in beef production has forced us to introduce new preventive methods. Vaccinations could contribute to the solution, but the high incidence of BRD already at an early age has made it difficult to introduce suitable vaccination programs. Challenge studies have shown promising results in 3-14 day old calves vaccinated with intranasal BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In one calf unit, 497 calves (mean age 19 days) were included in a study, 247 of which were vaccinated at the time of arrival to the unit and 250 served as negative controls (non-vaccinated). Intranasal vaccination combined with older arrival age (17 days or older) resulted in a higher daily gain (47.8 g/day) compared with non-vaccinated calves (p = 0.003) (16). It is worth highlighting that some of these productivity benefits of vaccination may be due to the impact on subclinical disease, as described earlier (7,9).…”
Section: General Identified Opportunities To Overcome Vaccination Bar...mentioning
confidence: 86%
See 1 more Smart Citation
“…In one calf unit, 497 calves (mean age 19 days) were included in a study, 247 of which were vaccinated at the time of arrival to the unit and 250 served as negative controls (non-vaccinated). Intranasal vaccination combined with older arrival age (17 days or older) resulted in a higher daily gain (47.8 g/day) compared with non-vaccinated calves (p = 0.003) (16). It is worth highlighting that some of these productivity benefits of vaccination may be due to the impact on subclinical disease, as described earlier (7,9).…”
Section: General Identified Opportunities To Overcome Vaccination Bar...mentioning
confidence: 86%
“…A further study demonstrated preferential weight gain, compared with unvaccinated calves, for those intranasally vaccinated at a slightly older age than those at a younger age. The authors suggested that younger calves may have been less able to respond to the vaccination due to having an immature adaptive immune system, or inhibitory effects of maternal antibody (16).…”
Section: Combination Vaccination Opportunitiesmentioning
confidence: 99%
“…Colostrum antibodies may protect calves for long periods (up to 6 months) against some virus (BVDV and IBR); however, they will have a short half‐life for other pathogens such as BRD bacteria, BRSV and PI3 (Fulton et al., 2004 ; Prado et al., 2006 ; Chamorro et al., 2014 ). This can be mitigated by the use of intra‐nasal vaccination against BRSV and PI3 in very young calves (Masset et al., 2020 ; Sandelin et al., 2020 ). Appropriate feeding of calves is another key aspect.…”
Section: Assessmentmentioning
confidence: 99%